The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1680/jinam.17.00014
|View full text |Cite
|
Sign up to set email alerts
|

Scottish cycling pavement assessment using hand–arm vibration exposure

Abstract: A defective pavement surface discourages cyclists from selecting certain routes and vibration exposure is a noticeable consequence of reduced path surface quality. Current asset management practice includes walkover surveys and cyclists reporting defects direct to the local authority. The research proposes the use of an instrumented probe bicycle to collect data for the assessment of pavement condition and rider comfort. Furthermore, the collection of hand-arm vibration exposure data is proposed as a means of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
4
1
Order By: Relevance
“…The findings of this paper are aligned with those of (Duc et al 2016) who showed that ELV for hand arm vibration was exceeded during a cobbled road cycling event. However, the vibration exposure values presented here are significantly greater than those observed in cycling on a range of surfaces on a commuting bicycle (Taylor et al 2018). This suggests that mountain bike athletes are at an increased risk of exposure to potentially harmful levels of hand arm vibration, particularly when taking a longer-term view of chronic exposure.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…The findings of this paper are aligned with those of (Duc et al 2016) who showed that ELV for hand arm vibration was exceeded during a cobbled road cycling event. However, the vibration exposure values presented here are significantly greater than those observed in cycling on a range of surfaces on a commuting bicycle (Taylor et al 2018). This suggests that mountain bike athletes are at an increased risk of exposure to potentially harmful levels of hand arm vibration, particularly when taking a longer-term view of chronic exposure.…”
Section: Discussioncontrasting
confidence: 54%
“…Focussing on performance athletes, they considered the application of European Directive 2002/44/EC (EC 2002) in defining the limits of exposure and action 'triggers' for safe exposure management in sport with particular reference to the exposure action value (EAV; 2.5 ms -2 ) and the exposure limit value (ELV; 5.0 ms -2 ). In a limited number of studies on road cycling, harmful levels of hand-arm vibration have been reported when riding on cobbled surfaces where exposure limit values (ELV) values are exceeded in less than 20 minutes (Chiementin et al 2013;Duc et al 2016;Taylor et al 2018). This is particularly concerning as riders competing in races such as the Paris-Roubaix spend ~90 minutes riding on cobblestones and are therefore subjected to harmful levels of hand-arm vibration.…”
Section: Introductionmentioning
confidence: 99%
“…therefore, it is suggested to strictly follow the instruction given in standards (Griffin, 1990;ISO-2631ISO- , 1997Taylor et al, 2017). For example, Taylor et al (2018) have proposed a standard procedure and equipment for measuring cycling vibration. A VBOX sport data logger was installed on the right handlebar, as shown in Fig.3 (b).…”
Section: Cycling Vibration Testmentioning
confidence: 99%
“…(3) vibration transmissibility of bicycles, bicycle components, and cycling apparel [14][15][16][17][18][19]; (4) assessments of road surfaces [20][21][22][23][24]; (5) cyclists' sensory perception [2,[25][26][27].…”
Section: Introductionmentioning
confidence: 99%